2015
DOI: 10.1080/21623996.2015.1084084
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial STAT3 and reactive oxygen species: A fulcrum of adipogenesis?

Abstract: The balance between cellular lineages can be controlled by reactive oxygen species (ROS). Cellular differentiation into adipocytes is highly dependent on the production of ROS to initiate the process through activation of multiple interlinked factors that stimulate mitotic clonal expansion and cellular maturation. The signal transducer and activator of transcription family of signaling proteins have accepted roles in adipogenesis and associated lipogenesis. Non-canonical mitochondrial localization of STAT3 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 63 publications
0
10
0
1
Order By: Relevance
“…The defects in mitochondria may enhance ROS generation and thus promote JNK and sterol-regulatory element binding proteins (SREBP) activation in neurons that results in neurodegeneration through the accumulation of lipid droplets [54]. The adipogenesis could also be influenced by ROS via signal transducers and activators of transcription 3 (STAT3) [55]. However, antioxidants could rescue the apoptosis [56].…”
Section: Neurodegenerationmentioning
confidence: 99%
“…The defects in mitochondria may enhance ROS generation and thus promote JNK and sterol-regulatory element binding proteins (SREBP) activation in neurons that results in neurodegeneration through the accumulation of lipid droplets [54]. The adipogenesis could also be influenced by ROS via signal transducers and activators of transcription 3 (STAT3) [55]. However, antioxidants could rescue the apoptosis [56].…”
Section: Neurodegenerationmentioning
confidence: 99%
“…While acting primarily as nuclear transcription factors, STAT proteins reportedly exert extranuclear functions (Meier and Larner, 2014). STAT3 phosphorylated at serine 727 (S727) is transported to mitochondria and stimulates mitochondrial function by activating complexes I and II of the electron transport chain (Wegrzyn et al, 2009;Kramer et al, 2015). We therefore asked whether Mk-biased HSCs express higher levels of pSTAT3 (S727) using flow cytometry.…”
Section: Mitochondria-associated Pstat3 Is Upregulated In Mitochondrimentioning
confidence: 99%
“…56 Studies using rat pancreatic insulin-producing INS-1E beta cell lines have reported that TRAF2 is required for the IFNγstimulated phosphorylation of STAT3 and that TRAF2 knockdown increases the cytokine-induced production of ROS. 61 Mitochondrial pSTAT3 Ser727 has been shown to be important in the growth/survival of cancer and its function is distinct from nuclear transcriptional regulation. 58 Thus, TRAF2 may be an important mediator of mitochondrial TNFR2/pSTAT3 Ser727 signaling.…”
Section: Cd133+mentioning
confidence: 99%
“…60 Indeed, STAT3 can act as a positive or negative regulator of mitochondrial activity depending on specific modifications. 61 Mitochondrial pSTAT3 Ser727 has been shown to be important in the growth/survival of cancer and its function is distinct from nuclear transcriptional regulation. 17,62 pSTAT3 Ser727 but not pSTAT3 Ty705 is crucial for the optimal activity of complexes I/II of the ETC regulating ROS concentrations and metabolic function.…”
Section: Nk-cd133+ Cells Ccrcc-cd133+ Cscsmentioning
confidence: 99%